Addition of Vegetable Oil to Improve Triterpenoids Production in Liquid Fermentation of Medicinal Fungus Antrodia cinnamomea - Linghui Meng; Biaobiao Luo; Yang Yang; Mohammad Omar Faruque; Jiuliang Zhang; Xiaohua Li; Xuebo Hu (Journal of Fungi, 2021)
The liquid fermentation of Antrodia cinnamomea is a promising alternative source for fungus production compared to the wildly grown fruiting body. Elicitation is a strong tool to enhance the productivity in microbial cells to obtain more compounds of interest. In this study, in order to improve the fungus growth and its terpenoids production, various vegetable oils were added in the fermentation broth of A. cinnamomea. It was found that corn oil from a group of vegetable oils exhibited the best effect on the biomass and triterpenoid content. After optimization, the initial addition of 1% (v/v) corn oil plus the inoculation of 10% (v/v) mycelia led to a maximum triterpenoid yield (532.3 mg L−1), which was increased as much as fourfold compared to the blank control. Differential transcriptome analysis demonstrated that corn oil significantly enriched several metabolic pathways including glycolysis/gluconeogenesis, propanoate metabolism and transmembrane hydrophobins. The enriched pathways interacted with deferentially expressed genes (DEGs) induced by corn oil treatment. Our research provides a potential strategy for the large production of triterpenoids by the improved fermentation of A. cinnamomea.